Persistence of maternal antibodies in calves born of combined foot-and-mouth disease + haemorrhagic septicaemia vaccinated buffaloes at organized dairy farm - PANGHAL, RITU; DAHIYA, SWATI; GUPTA, AKHIL KUMAR; SHARMA, VISHAL; BANGAR, YOGESH; KAKKER, NARESH KUMAR (The Indian Journal of Animal Sciences, 2023)
Twelve apparently healthy and recently parturiated Murrah buffaloes, vaccinated with Foot-and-mouth disease (FMD) + Haemorrhagic septicaemia (HS) combined vaccine at an organized farm along with their newborn calves were inducted for detection of antibodies in serum and colostrum against FMD virus (FMDV) serotypes O, A and Asia-1, and Pasteurella multocida using enzyme linked immunosorbent assay. The calves born to vaccinated dams showed the presence of protective maternal antibody titre (≥1.8 log10) from birth till the period of study (16th week of age) against FMDV serotypes O, A and Asia-1. The maternal antibody titre against P. multocida were protective (≥1.8 log10) till fifth day of age which became partially protective thereafter till the period of study. It is recommended to avoid vaccination of the calves before 16th week of age with FMD+HS combined vaccine.